2011
DOI: 10.1016/j.jcm.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A possible correlation between vitamin D deficiency and loss of smell: 2 case reports

Abstract: Objective: The purpose of this report is to present 2 cases of diminished olfaction that improved with increasing serum levels of vitamin D3. Clinical Features: Both patients were under the care of medical and chiropractic physicians for various complaints. A 47-year-old hyposmic woman was diagnosed with vitamin D deficiency who incidentally noticed a progressive return of her sense of smell while taking vitamin D supplements as prescribed by her medical doctor. A 34-year-old anosmic woman noticed a direct rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…In the literature, limited studies have investigated Vitamin D deficiency and its relationships with smell and showed similar findings. For example, a study of a few reported cases showed that olfactory dysfunction has subjectively been detected in adult patients with Vitamin D deficiency and it was improved with increasing serum Vitamin D [22]. Another study found that low serum (25(OH)D) concentrations were independently associated with olfactory dysfunction among Parkinson's disease patients [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, limited studies have investigated Vitamin D deficiency and its relationships with smell and showed similar findings. For example, a study of a few reported cases showed that olfactory dysfunction has subjectively been detected in adult patients with Vitamin D deficiency and it was improved with increasing serum Vitamin D [22]. Another study found that low serum (25(OH)D) concentrations were independently associated with olfactory dysfunction among Parkinson's disease patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…Ample epidemiological studies showed that Vitamin D deficiency is associated with brain health including cognitive function, neuropsychiatric disorders [34] and mood regulation [7][8][9]. This stems from the fact that Vitamin D receptors are widely spread throughout the central and peripheral nervous systems and have an impact on various neurotransmitters [12,13,22,34]. Some animal studies have shown that the rat olfactory system contains numerous target sites of Vitamin D receptor [17,35], which emphasizes the unique functional importance of 1,25-dihydroxy Vitamin D3 in olfactory function [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted by Grant, et al [31], a key observation was the decrease in the production of proinflammatory Th1 cytokines, such as TNF-α, and IFN-γ. Likewise, a study conducted by Jeffery et al [32] noted inhibition of T cell inflammatory cytokine production, specifically, a decrease in the cells producing IFN-γ. A report by Kruse and Cambron [33] presented two cases of an increased ability to smell after intervention through vitamin D supplements.…”
Section: Vitamin Dmentioning
confidence: 93%